Do Hong Kong SAR and China Constitute An Optimal Currency Area? : An Empirical Test of the Generalized Purchasing Power Parity Hypothesis - Liang, Hong (IMF Working Papers; Working Paper, 1999)
The paper explores the behavior of the long-run real exchange rate (RER) of Hong Kong SAR and China by testing the generalized-purchasing power parity hypothesis (G-PPP). The hypothesis argues that if the fundamental variables determining RERs are sufficiently integrated, as in a currency area, the RERs should share common trends. The findings of this study suggest (1) at present, Hong Kong SAR and China do not satisfy the conditions necessary for forming an optimal currency area by themselves; (2) when Japan and the United States are added to the group, common trends can be found; and (3) the long-run elasticity between the RERs of Hong Kong SAR and China is negative.